1986
DOI: 10.1002/eji.1830161202
|View full text |Cite
|
Sign up to set email alerts
|

Identity between human interferon‐γ and “macrophage‐activating factor” produced by human T lymphocytes

Abstract: Human peripheral blood monocytes purified by counterflow elutriation were activated in vitro by human natural or recombinant interferon-gamma (IFN-gamma) as shown by enhanced killing of Listeria monocytogenes and increased production of H2O2 in response to phorbol myristate acetate. Half-maximal stimulation for macrophage activation (MAF) was observed with 10-20 antiviral U/ml of purified recombinant IFN-gamma. These MAF activities were found to correlate with the antiviral activity dependent on IFN-gamma unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Both the proliferation assay and the measurement of IFN-g production are classical means of studying cellular immunity. The early functional tests also measuring IFN-g action are known as MIF or MAF (macrophage inhibiting or activating factors) tests [9][10][11]. In this study we measured IFN-g protein by an EIA modification based on two commercial monoclonal antibodies which was able to detect IFN-g in all supernatants from stimulated HSV lymphocytes, but all samples from non-immune subjects were below the detection limit of 50 pg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Both the proliferation assay and the measurement of IFN-g production are classical means of studying cellular immunity. The early functional tests also measuring IFN-g action are known as MIF or MAF (macrophage inhibiting or activating factors) tests [9][10][11]. In this study we measured IFN-g protein by an EIA modification based on two commercial monoclonal antibodies which was able to detect IFN-g in all supernatants from stimulated HSV lymphocytes, but all samples from non-immune subjects were below the detection limit of 50 pg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Human Blood Cells. Peripheral blood mononuclear neutrophils, eosinophils, T lymphocytes, monocytes, and PBMC were purified from single donor leukopacks (American Red Cross, Rockville, MD) as previously described (22)(23)(24).…”
Section: Methodsmentioning
confidence: 99%
“…This increased metabolic capacity has been related to the enhanced antimicrobial and cytotoxic activity of IFN-y-treated macrophages (2,7,8), and has been considered a biochemical correlate of macrophage activation (9). It was shown that human macrophages have to be treated with IFNy for a few days to develop maximum responsiveness to PMA, suggesting the involvement of an inductive process (1,6).…”
Section: Introductionmentioning
confidence: 99%